Efficacy and safety of intragastric balloon therapy compared to a multidisciplinary weight loss program (OPTIFAST) in a real-world population: a propensity score matching analysis - Oster, Miriam; Hein, Nathalena; Aksan, Aysegül; Krammer, H.; Theodoridou, Sophia; Stein, Jürgen (Obesity facts, 2023)
Introduction: Obesity is a major global health problem associated with comorbidities such as diabetes, cardiovascular disease, and cancer. Bariatric surgery is recognized to be the most effective weight loss intervention, but it is highly invasive and costly and can have serious side effects. Intragastric balloon (IGB) placement by endoscopy and hypocaloric diets are among a number of techniques that have been used in patients unsuitable for, or unwilling to undergo, obesity surgery. In this study, we compared the efficacy, safety, and cost-effectiveness of the hypocaloric OPTIFAST program (OPT) with endoscopic IGB placement for weight loss. Methods: In this retrospective observational cohort propensity score-weighted comparison (performed May 2014 to December 2020), participants with a BMI of 30-55 kg/m2, aged 18-70 years, were randomized to OPT or IGB for 26 weeks, followed by a weight maintenance phase. Patients were matched according to age, gender, and BMI. The study outcomes were percentage excess body weight lost, total body weight lost (TBWL), and percentage TBWL (%TBWL). Results: A total of 148 participants (75% of those randomized; 74 OPT, 74 IGB) made up the ITT population. Mean age was 44.1 ± 10.4 years, and the patients were predominantly female (77%). Baseline BMI was 44.1 ± 10.4 kg/m2. At 26 weeks, %TBWL in the OPT group was 19.6 ± 6.8% versus 11.9 ± 6.7% for IGB (p < 0.001). At 52 weeks, %TBWL for OPT was 18.2 ± 9.0% versus 12.0 ± 6.6% for IGB (p < 0.001). The OPT cohort also experienced significantly fewer adverse events compared with the IGB group. Conclusion: IGB placement and OPT induce clinically meaningful weight loss. However, OPT appears to induce clinically superior weight loss and has economic advantages through lower rates of complications and adverse events.